Metode Pemberdayaan Keluarga Dalam Vaksin Boster Covid 19 Melalui Interpersonal Relations dan Gender Mainstrem - Sutiyono (LPPM AN Nuur, 2022)
Background: The low vaccine coverage is due to low public awareness of health. The existence of low awareness requires appropriate empowerment methods. One method of empowerment can be implemented with the method of interpersonal relations and gender mainstream. Purpose: The purpose of empowering this learning method is to provide teaching in the provision of stimuli (instructions), individual responses (behavior) and consequences (behavior). Method: The method used in this service is to use the method introduction stage in the COVID-19 booster vaccine through interpersonal relations and gender mainstream in Mayahan Village, Grobogan Regency. Results : The results of service in the learning method can be seen from the learning achievements of the 100% running learning program socialization, 100% instructional education, 100% interpersonal relations method, 100% mainstrem gender method, 100% behavioral response, and the consequences and results of the empowerment method. 100%. Conclusion: There are better changes in the stimulus (instructions), individual responses (behavior) and consequences (behavioral consequences) of the COVID-19 booster vaccine method through interpersonal relations and gender mainstream in Mayahan Village, Grobogan Regency